A-priori analysis of an alternative wrinkling factor definition for flame surface density based Large Eddy Simulation modelling of turbulent premixed combustion. Issue 1 (2nd January 2019) - Klein, Markus; Chakraborty, Nilanjan
ABSTRACT: This paper discusses an alternative definition of the wrinkling factor and the resolved component of flame surface density (FSD) in the context of Large Eddy Simulations (LES) modelling of turbulent premixed combustion. The performances of conventional and an alternative definition of wrinkling factor are compared by employing a-priori analysis using explicitly filtered direct numerical simulation (DNS) data of statistically planar turbulent premixed, flames. It is demonstrated that the alternative definition of wrinkling factor can be used as well as the conventional definition to model the sub-grid scale flame wrinkling. The conventional definition of the wrinkling factor and resolved FSD might be more satisfactory from a theoretical point of view but the alternative definition has the advantage that the resolved FSD is no longer an unclosed expression and artificial flame thickening can be avoided without referring to an implicit counter-gradient transport closure.